Physical chemistry - Gordon M Barrow (New Delhi McGraw Hill Education, 2009)
The book is designed for an undergraduate course on Physical Chemistry taken by all undergraduate students of chemistry. The objective of the book is to help the students deal with various concepts of physical chemistry without an obscuring mathematical screen.
Keywords: Physical chemistry